Coordinated Integration And System Optimisation Of Air-Purification Technologies Through Mathematical Modelling - Djurayev Sherzod Sobirjonovich (Genius Journals, 2025)
Growing public-health pressure for ultra-clean air has stimulated a shift from single-device solutions to integrated treatment trains that combine cyclones, wet scrubbers, electrostatic precipitators and fabric filters. We present a unified dynamic model that (i) couples particle, gas and energy balances across each module, (ii) embeds a finite-volume discretisation for axial dispersion, and (iii) links the sub-models with continuity conditions for mass-flow, temperature and pressure. A multi-objective NSGAII optimiser is wrapped around the model to maximise overall removal efficiency while minimising pressure drop and annualised operating cost. Simulations show that coordinated operation adds up to 27 % efficiency gain at equal pressure drop compared with the best single device. Two illustrative results are given in Figure 1 (efficiency versus flow rate) and Figure 2 (Pareto frontier).
Keywords: Air-pollution control; hybrid filtration; pressure drop